Cuba’S Farming Market: Opportunities for Development - Saez-Tonacca, L (Taylor and Francis, 2023)
The structure of the food production and marketing system in Cuba is organized mainly through production cooperatives. This chapter examines the connection of farmers to markets and the opportunities for the creation of value chains and new markets linked to local farms in two areas of Cuba’s Sierra del Rosario and Cuchillas del Toa Biosphere Reserves, due to their high potential for cultivated biodiversity, especially in mamey and coconut crops, respectively. Other fruits and vegetables from these protected areas are being marketed (formally and informally) in local fairs and markets. It also shows the impact of the COBARB project in the Yateras area, which helped connect farmers in this area with the local market in Guantánamo. The development of participatory certification systems for organic products, the growing role of women in the creation of small businesses, as well as in the leadership of production and marketing initiatives, are all opportunities to increase market value, particularly regulation of organic agriculture. © 2024 selection and editorial matter, Urbano Fra Paleo and Leonor Castiñeiras; individual chapters, the contributors.